The Mayor's Political Leadership in HIV/AIDS Prevention and Control in Pekanbaru City - Prihati Prihati; Arizal Arizal; Alexsander Yandra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The AIDS Commission (KPA) is an institution formed in 2013 that has the function of leading, managing and coordinating efforts to prevent and control the Human Immunodeficiency Virus (HIV)/Acquired Immunodeficiency Deficiency Syndrome (AIDS) which is chaired directly by the Mayor of Pekanbaru. This paper aims to understand, examine in-depth and explain how the Mayor's leadership is in the prevention and control of HIV/AIDS in Pekanbaru, including Regional Apparatus Organizations, Health Organizations and Non-Governmental Organizations. This study uses a qualitative method with informant withdrawal techniques through Stratified Sampling, converted to the Snow Ball technique. This study showed that the mayor leadership in preventing and overcoming AIDS was autocratic due to the policies were made in the form of mayor regulations. The decisions were made only from the Mayor, causing weaknesses including unclear policy objectives, budgeting, and ambiguity regarding oversight by the legislative institution (DPRD) of Pekanbaru. It has an impact on communication, resources, disposition and bureaucratic structures.